Antenna design for problems area in Shah Alam - Poniran, Zalizah; Tukirin, N. Aishah (1993)
This project is about the television antenna design that can solve the channel reception problems in Section 8, Shah Alam. In order to design a good antenna reception, a study of the antenna characteristic and rendom survey to a certain area in Shah Alam is needed to acknowledge the current problem.